Numerical analysis of CdTe–carbon hybrid nanofluid flow with fractal-fractional derivatives in a radiative MHD channel - A. Agathiyan; K. Varatharaj; V. Sathishkumar; B. Vinothkumar; Ali Akgul; Murad Khan Hassani (Modeling Earth Systems and Environment, 2026)

Therapeutic potential of fruit mulberry: a systematic review of pharmacological activities and mechanistic insights - P. Lokeshkumar; R. Shanmugam; K. A. Murugesh; B. Vinothkumar; P. Jaisridhar (Phytochemistry Reviews, 2026)

Unravelling the Multifaceted Action of Chaetomium globosum Cg6 Enriched with Plant Herb Against Early (Alternaria solani) and Late Blight (Phytophthora infestans) Pathogens Infecting Potato - S. Sharnika; L. Rajendran; G. Karthikeyan; B. Vinothkumar; P. Raja; K. Saravanakumari; D. Durgadevi (Potato Research, 2025)

Exploitation of Chaetomium globosum and AMF against Macrophomina phaseolina causing root and crown rot in strawberry and its underlying mechanisms by molecular docking - I.S. Jothini Varsha; L. Rajendran; K. Saravanakumari; G. Karthikeyan; B. Vinothkumar; R. Anandham (Physiological and Molecular Plant Pathology, 2025)

Evaluation and Validation of IPM Modules in Potato Against Invasive Leaf Miner, Liriomyza huidobrensis - Monica S. S.; Vinothkumar B. (Potato Research, 2024)

Untangling the taxonomic ambiguities of the spotted seerfish Scomberomorus guttatus with the description of a new species from India - Eruppakkottil M. Abdussamad; Thomas Toji; Amalraj M. R. Margaret; Kalappurakkal G. Mini; Kothanahally M. Rajesh; Pokkathappada A. Azeez; Vinothkumar Ramar; Thayichira B. Retheesh; Athikkattil M. Abbas; Ismail Shihab; Sneha M. George; Rohith Prathibha; et al. (Journal of Fish Biology, 2024)
Scomberomorus guttatus has been subjected to a series of synonym assignations over the years. Its taxonomy has been mired with ambiguities due to the greater‐than‐average morphological variations observed in samples from different regions. An integrated taxonomic revision with molecular support indicated that the species that was thought to be a single entity, in reality, is a complex of three distinct species. They are morphologically distinct with respect to the body depth and elongation, cephalic morphometry, and meristic characteristics. Otolith morphometry and phylogenetic evidence further established the taxonomic divergence within the spotted seerfish complex. The phylogenetic characteristic as indicated by the mitochondrial Cytochrome c Oxidase subunit I (COI) sequence unveiled that S. guttatus had a high intraspecific divergence of 11.1% from its two identical congeners and a divergence of 2.34% between the congeners, indicating scope for categorizing them as separate species. Based on the morphological and molecular evidence, S. guttatus is redescribed; the senior synonym Scomberomorus leopardus is resurrected as a valid species; and a new species Scomberomorus avirostrus n. sp. is described with keys for species distinction.

Isolation and characterization of heterotrophic nitrification–aerobic denitrification and sulphur-oxidizing bacterium Paracoccus saliphilus strain SPUM from coastal shrimp ponds - Y. D. Jaffer; H. Sanath Kumar; R. Vinothkumar; A. B. Irfan; N. M. Ishfaq; Parvaiz Ahmad Ganie; Raja Adil Hussain Bhat; A. Vennila (Aquaculture International, 2019)